ANALISIS TINGKAT KEBISINGAN ARUS LALU LINTAS DI SIMPANG GELORA SAMADOR KOTA MAUMERE, NUSA TENGGARA TIMUR - Anastasia Merdekawati Noralita Soludale; Cornelia Hildegardis; Maria Carolin Tandafatu; Febriyanti Alwisye Wara (ITB Ahmad Dahlan Jakarta, 2022)
Noise is noise pollution that interferes with daily life. One source of noise comes from the flow of vehicle traffic. There are many office buildings and residential houses around the Gelora Samador intersection, Maumere City, it is necessary to conduct research to analyze the noise level of traffic flow. The method used in this study is to place a Sound Level Meter measuring instrument at several points around the Gelora Samador intersection, and from the measurement results it is analyzed to obtain the noise level of traffic flow. The results of this study indicate that the noise level that occurs exceeds the noise threshold standardized in KEP.48/MENLH/II/1996, so it is necessary to control efforts that can reduce the noise level that occurs, including the placement of vegetation, as well as the design of a sound barrier that can applied to the path itself.